IL MS. LEIDENSIS VOSSIANUS LATINUS F. 25 NELLA TRADIZIONE MANOSCRITTA DI VIRGILIO - Giuseppe Ramires (Exemplaria Classica, 2013)
The ms. Leidensis Voss. F. 25, written in France in the late ninth or early tenth cen- tury, contains the works of Virgil and the commentary by Servius. The manuscript, which belonged to Alexandre Petau and to Queen Christina of Sweden, may have come from the Monastery of Fleury. The present paper includes an examination of its relationship with the manuscript tradi- tion of Virgil, both ancient and medieval. Study of the most interesting variants.